Dinamika Hukum Islam Dalam Konfigurasi Politik Hukum di Indonesia - Rahmi Hidayati (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2010)
The article examines the dynamic of slamic political law in indonesia. within the history of indonesia, the efforts to imlement islamic law have experienced ebb and flow. it strongly depends on the size of electoral vote gained by islamic political parties to put their representaves at the parliement. it implies, therefore without political support the implementation of islamic law would remain inconceivable. the better the relationship between islam and politics, the greater the chances for the implementation of islamic law. however, the more distant the relationship between them, the smaller the chances for the implementation of islamic law.